Influence of green tea polyphenols on the colloidal stability and gelation of WPC - Von Staszewski, Mariana (2011)
Green tea extracts are being widely used in food products due to their health-promoting properties. Polyphenols can interact with food proteins leading to the formation of soluble or insoluble complexes; therefore they could alter functional properties of proteins. The objective of the present work was to study the colloidal stability and gelation characteristics of a whey protein concentrate (WPC) in the presence of green tea polyphenols. Mixtures of WPC35 (8 and 30% w/v) and green tea polyphenols (0.25-1% w/v) were prepared at pH 4.5 and 6.0. The size of particles formed was analyzed by light scattering, while gelation was characterized by means of dynamic rheometry and texture analysis of gels. At pH 6.0, the particles were smaller and had a higher net charge than at pH 4.5, which accounted for by a less precipitation of the system at pH 6.0. The G' parameters of gels upon cooling at 35 °C increased with increasing polyphenols concentration at both pH values. However, the relative viscoelasticity decreased. The texture analysis indicated that the addition of polyphenols improved the firmness and adhesiveness of the gels at pH 6.0, while no significant differences were seen at pH 4.5. The results obtained in this work indicate that pH-dependent interaction between green tea polyphenols and WPC induces the formation of aggregates that modifies the viscoelastic and texture properties of the gels.